Entrepreneurial foresight as entrepreneurs’ transformative power: Inducing contextual change through opportunity formation - Djuricic, Ksenija (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2022)
In future-making activity, such as entrepreneurship, entrepreneurial agency is viewed as the transformative power to change the socio-economic structure on which it depends. Shaped by socio-economic circumstances, entrepreneurial agency is also highly contingent on the agency of other humans, both of which create high complexity and a wide array of indeterminate possibilities for entrepreneurial agency to change the existing socio-economic structure. Therefore, entrepreneurial agency should be observed through entrepreneurs’ capacity to engage in structural transformation by acting upon complex relationships between structure and human agents and facing simultaneously the openness of the future. Yet, a lack of knowledge about how entrepreneurs tame such complexity and indeterminacy as well as differing perspectives on entrepreneurial agency deriving from a longstanding debate around how entrepreneurs form opportunities require a deeper understanding of how entrepreneurs employ their transformative power to change their operating structure. Therefore, this dissertation addresses the phenomenon of entrepreneurial agency in opportunity formation by proposing that entrepreneurs’ transformative power lies in their capacity for foresight in considering the complexity of their operating environment and anticipating the future. Drawing upon the foresight literature, this dissertation frames entrepreneurial foresight as individual entrepreneurs’ capacity to structure knowledge of the temporal–spatial aspects of the contexts in which they move and operate and to process such knowledge based on their own experience of time. While acknowledging that entrepreneurs ultimately induce structural transformation, this dissertation argues that the change entrepreneurs create begins within their operating contexts. Moreover, this dissertation argues that change emerges in entrepreneurial opportunities, which are entrepreneurs’ visions of novel contexts. However, due to a number of underdeveloped concepts in the entrepreneurship research, such as knowledge, time and temporality in entrepreneurial activity and opportunity formation, interchangeable views of entrepreneurial opportunities as ideas or visions, and the unclarified concept of entrepreneurial foresight, a more synthesized approach to these concepts is needed. Therefore, to address this complex phenomenon and to synthesize and clarify a number of incoherencies and missing points, this dissertation relies on Giddens’ concepts of agency, contexts and time–space. Based on the theoretical knowledge and empirical findings, I have summarized my key findings into three subpropositions. First, I argue that entrepreneurial opportunities represent entrepreneurs’ subjective visions of the novel contexts. In these visions, structural properties and agents’ activities from previously known existing contexts are processed and combined in such a way that they produce a change in the agents’ behaviour.. Second, I state that in opportunity formation knowledge is always spatial first, but once it leads entrepreneurs to frame their contexts, knowledge reveals its temporal aspects that when processed feed entrepreneurs’ subjective perceptions of the opportunities’ future existence. Third, I contend that entrepreneurial foresight represents entrepreneurs’ cognitive capacity that allows structuring of the operating contexts as systems, envisioning future contexts, and supports objective and subjective evaluation of the potential of the newly envisioned contexts’ future existence. These three subpropositions jointly illustrate the building blocks of entrepreneurial foresight as entrepreneurs’ transformative power to induce contextual change through opportunity formation. Accordingly, to answer the main research question and fulfil the main aim of this dissertation, my main proposition is that when forming opportunities, entrepreneurs employ foresight to cognitively process and systemically structure acquired knowledge of the contexts and subjectively experience the temporal and spatial aspects to create futures knowledge. This interdisciplinary research brings new insights to the entrepreneurship and foresight research. In uncovering entrepreneurs’ agentic power in inducing change within the contexts throughout which they move, this dissertation provides deeper topical knowledge of the relevant concepts in the entrepreneurship and foresight literature. Moreover, this research provides some practical implications for entrepreneurs, entrepreneurship educators and advisers and other actors who support entrepreneurship.

Yrittäjämäinen ennakointi yrittäjien muutosvoimana Tulevaisuutta luovassa toiminnassa, kuten yrittäjyydessä, yrittäjämäinen toimijuus nähdään muutosvoimana, joka muokkaa sosioekonomista rakennetta, josta yrittäjyys on riippuvainen. Sosioekonomisten olosuhteiden muovaama yrittäjämäinen toimijuus on myös erittäin riippuvainen muiden ihmisten toiminnasta. Yhdessä nämä luovat monimutkaisuutta ja laajan valikoiman määrittelemättömiä mahdollisuuksia yrittäjämäiselle toimijuudelle muuttaa vallitsevaa rakennetta. Yrittäjämäistä toimijuutta tulisikin tarkastella yrittäjien kykynä osallistua rakenteelliseen muokkaamiseen, kun he hyödyntävät rakenteiden ja inhimillisten tekijöiden monimutkaisia suhteita kohdatessaan avoimen tulevaisuuden tarjoamia mahdollisuuksia. Puutteellinen tieto yrittäjien tavoista ottaa haltuun tällaista monimutkaisuutta ja epämääräisyyttä sekä pitkään jatkuneen keskustelun synnyttämät erilaiset näkemykset yrittäjien tavoista muodostaa mahdollisuuksia edellyttävät tarkempaa ymmärrystä siitä, kuinka yrittäjät käyttävät muutosvoimaansa muuttaakseen toimintaympäristöään. Tämä väitöskirja käsittelee yrittäjämäisen toimijuuden ilmiötä mahdollisuuksien muodostamisessa ja ehdottaa, että yrittäjien muutosvoima piilee heidän kyvyssään ennakoida toimintaympäristönsä monimutkaisuutta ja tulevaisuutta. Ennakointia käsittelevään kirjallisuuteen pohjautuen väitöskirja muotoilee yrittäjämäisen ennakoinnin yksittäisten yrittäjien kykynä jäsentää tietoa toimintakontekstinsa aikaavaruudellisista näkökohdista ja käsitellä tätä tietoa oman aikakokemuksensa perusteella. Vaikka aiemmin on tunnistettu, että yrittäjät saavat lopulta aikaan rakenteellisia muutoksia, tässä väitöskirjassa esitetään, että yrittäjien aikaansaama muutos alkaa heidän toimintaympäristöstään. Lisäksi väitöskirjassa väitetään, että muutos syntyy yrittäjämäisinä mahdollisuuksina, jotka ovat yrittäjien visioita uusista konteksteista. Useat yrittäjyystutkimuksessa käytettävät käsitteet ovat kuitenkin kehittymättömiä, kuten yrittäjämäistä toimintaa ja mahdollisuuksia koskeva tieto, aika ja ajallisuus, vaihtelevat näkemykset yrittäjämäisestä mahdollisuudesta ideana tai visiona sekä yrittäjämäisen ennakoinnin epäselvä käsite, ja niiden tarkasteluun on vaadittu aiempaa syntetisoidumpaa lähestymistä. Tällaisen monimutkaisen ilmiön käsittelemiseksi sekä useiden epämonimutkaisen ilmiön käsittelemiseksi sekä useiden epäjohdonmukaisuuksien ja puuttuvien kohtien selkiyttämiseksi ja syntetisoimiseksi tämä väitöskirja tukeutuu Giddensin toimija-, konteksti-, ja aika-avaruuskäsitteisiin. Olen tiivistänyt teoriaan ja empiirisiin havaintoihin perustuen keskeiset tulokseni kolmeen osaväittämään. Ensinnäkin väitän, että yrittäjämäinen mahdollisuus edustaa yrittäjän subjektiivista näkemystä uudesta kontekstista, jossa aiemmin tunnistettuja rakenteellisia ominaisuuksia ja toimijoiden toimintaa käsitellään ja yhdistellään siten, että ne muuttavat toimijoiden toimintaa. Toiseksi väitän, että mahdollisuuksien muodostuksessa tieto on aina ensin avaruudellista, kunnes yrittäjät muodostavat tiedosta omia kontekstejaan, jolloin tiedon ajallinen ominaisuus paljastuu. Tämä muokkaa yrittäjien subjektiivisia näkemyksiä mahdollisuuksien olemassaolosta tulevaisuudessa. Kolmanneksi väitän, että yrittäjämäinen ennakointi edustaa yrittäjien kognitiivista kykyä, joka mahdollistaa toimintakontekstien jäsentämisen järjestelmiksi, tulevaisuuden kontekstien visioinnin sekä visioitujen kontekstien potentiaalin objektiivisen ja subjektiivisten arvioinnin. Yhdessä nämä kolme osaväittämää havainnollistavat yrittäjämäisen ennakoinnin roolia yrittäjien muutosvoimana, joka mahdollisuuksia muodostamalla saa aikaan muutoksia yrittäjämäisen toiminnan kontekstissa. Täten keskeisin väittämäni väitöskirjan päätutkimuskysymykseen ja tavoitteen saavuttamiseksi on, että muodostaessaan mahdollisuuksia yrittäjät hyödyntävät ennakointia, jolla he prosessoivat kognitiivisesti ja jäsentelevät systemaattisesti konteksteista hankittua tietoa, ja joka tarjoaa subjektiivisen kokemuksen tiedon ajallisista ja avaruudellisista omaisuuksista, joilla yrittäjät luovat uutta tietoa tulevaisuutta varten. Tämän tutkimuksen poikkitieteellinen ote tuo uusia näkemyksiä yrittäjyyden ja ennakoinnin aloille. Väitöskirja osoittaa yrittäjämäisen toimijuuden voiman muutosten aikaansaamisessa konteksteissa joissa yrittäjät liikkuvat, ja tarjoaa uutta syvempää tietoa yrittäjyys- ja ennakointikirjallisuuden keskeisistä käsitteistä. Väitöstyö tarjoaa myös käytännön tietoa yrittäjille, yrittäjyyskasvattajille sekä yrittäjiä ja yrittäjyyttä tukeville toimijoille.